Tinjauan atas Desain Sampul Muka Buku Anak-Anak Revolusi Karya Budiman Sudjatmiko - Danu Widhyatmoko (Bina Nusantara University, 2014)
The cover design is the face of the whole picture of the publication works, which not only serves as a media promotion but also as a medium of identification. This paper consists of a review of the cover design of a book of Anak-anak Revolusi by Budiman Sudjatmiko by using visual communication design approach. Then the choice will also be discussed in other visual approach that can be applied. Research method used in this paper is literature study, continued with reflective data analysis. By the end of the paper, a more comprehensive picture related object being reviewed. The book of Anak-anak Revolusi by Budiman Sudjatmiko has an excellent script and has an appropriate methaporic book cover. However, at the time of the visualization of the book cover is executed, there are many shortcomings that should have been optimized so that the book of Anak-anak Revolusi could be presented entirely and completely in many aspects.